The flu and you - Rodda, Geri.; Rodda, Jim ([United States] : Pumpkin Hill Productions, 2006)
Basic instruction on the spread of the influenza virus, including preventive strategies and healthy habits to avoid illness.
Keywords: Influenza -- Juvenile literature